A Text Analytic on Dynamic Capability - Yudistira, Yudi; Arkeman , Yandra; Andati, Trias; Jahroh , Siti (International Journal of Economics, Business, and Entrepreneurship, 2022)
Business strategy is a variable that affects the use of financial and non-financial performance metrics by firms. Companies use financial and non-financial performance measurements as a source of information to make continuous changes. This constant improvement encourages the development of dynamic capabilities so that the business may compete effectively in an environment of intense competition. A company's business plan serves as a guide for enhancing its fundamental skills. Unique resources in the form of dynamic capabilities represent core competences. Companies have diverse dynamic capabilities. This distinction provides a corporation with a competitive advantage over its rivals. This study aims to identify the published development map and trend of Dynamic Capability from trustworthy sources. More than 873 Scopus-indexed research publications were reviewed. The export data is then processed and analyzed with the R Biblioshiny program to generate the development map for Dynamic Capability. According to the study's findings, the number of publications on the evolution of research's function continues to climb. In addition, the study draws a number of important findings about Dynamic Capability and the direction of future research development.